THE ROLE OF CHINESE IN COMING OF ISLAM TO INDONESIA: TEACHING MATERIALS DEVELOPMENT BASED ON MULTICULTURALISM - Kurniawan, Hendra (Paramita: Historical Studies Journal, 2017)
The aim of this research was to describe the role of Chinese in coming of Islam to Indonesia in XV-XVI century and developed it into a history teaching materials based on multiculturalism. It was a library research with historical approach. Data that were obtained from various sources analyzed by qualitatively descriptive into teaching materials integrated into curriculum. The results showed that there wereÂ  some historical facts, strengthen the role of Chinese in the coming of Islam to Indonesia in the XV-XVI centuries. The study compiled into teaching materials that can be integrated into curriculum 2013 on Indonesian History subjects for high school class X. Developed teaching materials can disseminated multiculturalism values in students to realize a harmonious society.Â Penelitian ini bertujuan mendeskripsikan peran Tionghoa dalam masuknya Islam ke Indonesia pada abad XV-XVI dan mengembangkannya menjadi bahan ajar sejarah berbasis multikulturalisme. Penelitian ini merupakan penelitian kepustakaan dengan pendekatan historis. Data yang diperoleh dari berbagai sumber dianalisis secara kualitatif deskriptif menjadi bahan ajar untuk diintegrasikan ke dalam kurikulum. Hasil penelitian menunjukkan bahwa terdapat berbagai fakta sejarah yang menguatkan peran Tionghoa dalam masuknya Islam ke Indonesia pada abad XV-XVI. Kajian tersebut disusun menjadi bahan ajar yang dapat diintegrasikan ke dalam Kurikulum 2013 pada mata pelajaran Sejarah Indonesia untuk SMA kelas X. Bahan ajar sejarah yang dikembangkan dapat menyemai nilai multikulturalisme dalam diri siswa untuk mewujudkan masyarakat yang harmonis.Â